Genetic diversity assessment of Hemibagrus nemurus from rivers in Java Island, Indonesia using COI gene - Agus Nuryanto; NUNUNG KOMALAWATI; SUGIHARTO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nuryanto A, Komalawati N, Sugiharto. 2019. Genetic diversity assessment of Hemibagrus nemurus from rivers in Java Island, Indonesia using COI gene. Biodiversitas 20: 2707-2717. Green catfish (Hemibagrus nemurus) is a popular freshwater fish that highly exploited in almost all the rivers in Java Island. The exploited population tends to have low genetic diversity. Meanwhile, separated populations might lead to a genetic difference among the river populations. This study aims to investigate the genetic diversity and population variation of H. nemurus collected at eleven rivers across Java Island. The analysis based on 465 bp fragment of the cytochrome c oxidase 1 gene from 140 individuals. Analysis of overall populations proved that H. nemurus had a high gene diversity (h= 0.935±0.016) and nucleotide diversity (? = 0.073±0.036). Within population analysis also showed that H. nemurus populations showed high levels of gene diversity (h= 0.338±0.128 to 1.000±0.022) and nucleotide diversity (? =0.001±0.001 to 0.071±0.038). Those diversity values indicated that H. nemurus had high level of genetic diversity, except for the Citanduy population. Population comparison showed that significant genetic differences observed among populations (p= 0.000 for both variance component and Fst-value). However, pairwise comparison analysis indicated complex pattern of population differentiation. The high genetic diversity and complex pattern of population differentiation have important implication for H. nemurus conservation in Java Island.